O TRATAMENTO DA INFORMAÇÃO (PCN) E A PROBABILIDADE E ESTATÍSTICA (BNCC): análise de algumas orientações - GILVANETHE MIGUEL PEDRO (2023)
This text is the final result of the non-disciplinary curricular component of oriented teaching activities, and aims to analyze some guidelines for teaching initial concepts of probability and statistics present in two official documents: National Curricular Parameters and National Common Curricular Base. A partial analysis of these two documents was carried out, then we also analyzed two textbooks to verify how these concepts were approached and how this could influence the teacher's practice in the classroom.